Heat shock protein 20 from Procambarus clarkii is involved in the innate immune responses against microbial infection. (May 2020) - Li, Chang-Sheng; Kausar, Saima; Gul, Isma; Yao, Xiao-Xiao; Li, Meng-Yi; Chen, Cheng-Chun; Abbas, Muhammad Nadeem; Dai, Li-Shang
Abstract: Small heat shock proteins (shsps) are conserved across invertebrate species. They are implicated in the modulation of various biological processes, such as immune responses, abiotic stress tolerance metamorphosis, and embryonic development. Herein, we identified a heat shock protein 20 from the red swamp crayfish, Procambarus clarkii (named as Pc-Hsp20), and performed in vivo studies to elucidate its physiological functions in the innate immunity. The open reading frame of Pc-Hsp20 was 609 base pair, encoding a protein of 202 amino acid residues with a hsp20/alpha crystallin family domain. Pc-Hsp20 was ubiquitously expressed in various tissues; however, it was highest in the hepatopancreas. The challenge with immune elicitors remarkably enhanced the transcript level of Pc-Hsp20 in the hepatopancreas when compared with the control. Administration of double-stranded RNA could significantly reduce expression of the Pc-Hsp2 0 mRNAs, and most of the immune-related genes expression enhanced with a variable concentration in the hepatopancreas. Altogether, these results suggest that Pc-Hsp20 may participate in innate immunity against microbial pathogens. Highlights: A Heat shock protein 20 from Procambarus clarkii ( Pc-Hsp20 ) was identified and characterized for the first time. The expression patterns of Pc-Hsp20 under immune challenges were investigated. RNA interference of Pc-Hsp20 influenced the expression of immune-related genes.